ENVIRONMENTAL REGULATORY STRINGENCY, CORRUPTION, AND FDI: NEW EVIDENCE FROM A PANEL OF COUNTRIES - Ridzuan, Sulhi; Sarmidi, Tamat; Mohd Nor, Abu Hassan Shaari (Journal of Techno-Social, 2014)
Previous literatures on both studies of pollution haven and FDI-corruption nexus have produced inconclusive results. This study uses Generalized Method of Moments (GMM) to address potential endogeneity of independent variables and country-specific effects issues when assessing the relationship between foreign direct investment (FDI), stringency of environmental regulations and corruption. FDI inflows are found to be discouraged by stricter environmental regulations and high level of corruption will induce FDI. Surprisingly, we find new evidence that both effects are changed after each of them exceeds threshold levels. Countries have to pass the threshold levels in order to gain positive impact of both stricter regulations and low level of corruption.